Republic of Congo : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2012)
The government of the Republic of Congo launched a program aimed at consolidating peace and promoting economic and social development. The objectives included improvement of governance and consolidation of peace and security, promotion of growth and macroeconomic stability, improvement of public access to basic social services, improvement of the social environment, integration of disadvantaged groups, and combating HIV/AIDS. The review shows that much remains to be accomplished, and building on the significant gains of recent years, the decision to expand and strengthen the strategic poverty reduction framework was made.